Displacement and Articulation Rhetoric in Sa'adi's Golestān - Omer Mohammad Saeed; Parsa Yaghoobi Janbeh saraei (مطالعات زبانی و بلاغی)
In every text, there are two levels of ambiguity of translation and ratio, which are the basis of the rhetorical explanation of the text from different perspectives of textual analysis, whether formalistic or discursive. In most of the classical texts, the aforementioned levels of ambiguity more or less exist, but in some texts, one aspect outweighs the other. Sa’adi's Golestān is one of the texts whose rhetorical basis is based on the ambiguity of ratio and types of displacement and articulation. In this article, the rhetoric of Golestān or the confrontation of the author-narrator with the listener/reader is classified and interpreted based on the ambiguities of the relationship between the creator of the text in the form of displacement and the significance of linguistic-narrative articulations. The basis of the analysis is the concepts and terms of several communicative fields such as semantics, rhetoric, narratology and discourse analysis. The result shows that, according to the dominant aspect of ratio ambiguity in Golestān, the author-narrator of the text uses four levels of extension / floating, pre-information, connection / eclecticism and repetition/accumulation in order to convey meaning or communicate the "Message–Force." Some of these cases, while creating diversity, contain the type of openness and polyphony, which help to draw the attention of listeners/readers. In some cases, the direction-inhibition aspect of the text restrains the listener/reader under the support-control umbrella of the author-narrator. Of course, all cases considered, while directing the listeners/readers, in most cases the text leads them to an open state of reality, which does not limit inferences in the reader’s encounter with the textual and conceptual representations.